Attribution Analysis and Countermeasures of Silence Phenomenon in Public English Classes at Vocational Colleges - Deng, Wen (International Journal of Social Sciences and Public Administration, 2025)
Silence phenomenon in public English classes at higher vocational colleges in China poses a significant challenge to teaching quality and student development. This study investigates the multidimensional causes of classroom silence, focusing on student-related factors (weak foundational skills, utilitarian learning mindsets, and psychological barriers), teacher-related issues (outdated pedagogical methods and negative attitudes), and cultural-environmental influences (traditional values conflicting with modern educational needs and the marginalized status of English courses). This paper proposes targeted countermeasures which include fostering students’ metacognitive abilities through reflective practices, adopting student-centered teaching strategies (e.g., interactive activities and digital tools), enhancing institutional support via incentive mechanisms and teacher training, and promoting a culturally inclusive classroom environment. By addressing these factors holistically, the study aims to mitigate classroom silence, improve learner engagement, and advance pedagogical reforms in higher vocational English education.